2012
DOI: 10.1097/njh.0b013e3182516484
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Perceptions of Palliative Sedation in a Scottish Hospice

Abstract: Palliative sedation is a treatment of last resort to relieve intractable suffering that can be ethically controversial. There has been very little research into the nursing perspective. This study explored the knowledge, perceptions, and experiences of hospice nurses with palliative sedation. Semistructured interviews were conducted with a convenience sample of five hospice nurses in a Scottish hospice. Data were collected over 3 months and analyzed using Burnard's thematic content analysis method. The major t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(41 citation statements)
references
References 21 publications
7
34
0
Order By: Relevance
“…They believed that palliative sedation, even if required in large doses, could relieve suffering without 'killing' the patient, and recognised that the patient was dying of their underlying disease. The findings of Rietjens et al,' (2007) study in the USA also confirm those of Zinn and Moriarty (2012) in that seven nurse participants stated their belief that palliative sedation did not hasten the dying process. In contrast, Inghelbrecht et al,' (2011) extensive study found that 77% (n=4428) of the nurses thought that palliative sedation was partly or clearly intended to hasten death and only 4% believed that it actually had no lifeshortening effect.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…They believed that palliative sedation, even if required in large doses, could relieve suffering without 'killing' the patient, and recognised that the patient was dying of their underlying disease. The findings of Rietjens et al,' (2007) study in the USA also confirm those of Zinn and Moriarty (2012) in that seven nurse participants stated their belief that palliative sedation did not hasten the dying process. In contrast, Inghelbrecht et al,' (2011) extensive study found that 77% (n=4428) of the nurses thought that palliative sedation was partly or clearly intended to hasten death and only 4% believed that it actually had no lifeshortening effect.…”
Section: Introductionsupporting
confidence: 69%
“…Finally, while studies in this area are few, it would seem that nurses' views on whether or not palliative sedation therapy contributes to shortening life or hastening death can depend on the palliative care practices of the country in which they work. Zinn and Moriarty's (2012) qualitative study with five participants working in a Scottish hospice found that these nurses were satisfied that the level of medication was proportionate to the need to manage refractory symptoms. The research participants had no discomfort about administering increasing doses of medication when necessary to reduce suffering and reiterated that medication was carefully titrated until effective.…”
Section: Introductionmentioning
confidence: 99%
“…Nilsson and Tengvall (2013) interviewed 14 nurses in a specialist palliative care unit in Sweden and identified ethical concerns and also issues related to responsibility, confidence, communication, and teamwork. A study in Scotland by Zinn and Moriarty (2012) of the experiences of nurses carrying out palliative sedation identified three themes-suffering, courage, and peace-as representing how nurses believed that palliative sedation was sometimes necessary and appropriate to ensure a peaceful death. Seymour and colleagues (2007) conducted interviews with 14 nurses, 11 doctors, and 10 researchers.…”
Section: Introductionmentioning
confidence: 99%
“…They also mention total pain as a reason for PC sedation and that the care provided should ensure that the bereaved would not have memories of their loved ones dying in distress. 32…”
Section: Resultsmentioning
confidence: 99%
“…Communication, particularly in PC, is viewed as a natural principle, and communication skills training should be provided by the managers. 32,35,39,45…”
Section: Resultsmentioning
confidence: 99%